Application of Bio-fertilizers for Quality Seedling Production of Azadirachta indica A. Juss - Karthikeyan, A.; Maria Dominic Savio, M.; Deeparaj, B. (Indian Forester, 2007)
An experiment was conducted on Azadirachta indica A. Juss inoculated with bio-fertilizers under nursery conditions. The bio-fertilizers VAM fungi, Azospirillum and Phosphobacterium were inoculated individually or in various combinations in sterile soil along with A. indica seedlings. Then the seedlings were harvested at 120 days after transplantation. The biofertilizer inoculated seedlings resulted in increased plant height, root collar diameter and biomass. The combined microbial inoculations resulted in quality seedlings in nursery.